Патогенез порушення механізмів репарації пародонту після екстракції зубу за умов експериментального цукрового діабету - Ганчев, Кирило Сергійович; Ганчев, К. С.; Hanchev, K. S. (Запорізький державний медичний університет, 2019)
У роботі встановлено патогенетичні особливості стану системи монооксиду азоту, вродженої ланки місцевого імунітету та особливостей протікання регенерації тканин пародонту, визначені особливості стану кісткової тканини мандибули, мінералізації емалі й дентину молярів без екстракції зубу в різні періоди після його видалення на тлі експериментального цукрового діабету. Визначено, що у слизовій оболонці ротової порожнини щурів із цукровим діабетом формується ізоформний дисбаланс ферменту NOS, відмічаються нижчі вихідні значення вмісту та концентрації nNOS та еNOS, але значно вищі – іNOS, на фоні високого вихідного рівню нітритів. Доведено особливості експресії CD68 та Ki-67 в слизовій оболонці ротової порожнини щурів, які вказують на те, що цукровому діабету притаманна розповсюджена макрофагальна інфільтрація та висока проліферативна активність фібробластів, через що екстракція зубу незначно збільшує чисельність CD68-імунопозитивних макрофагів, але характеризується високою проліферативною активністю одразу після видалення зубу із максимальними значеннями Ki-67 на 14-у добу постекстракційного періоду. При цукровому діабеті загоєння альвеолярної лунки після видалення зубу відбувається неефективно через порушення резорбційно-репаративних взаємин, що проявляється зниженням показника радіологічної щільності в області альвеолярної лунки та інтеральвеолярно-радикулярних кісткових перетинок 1-го моляра, коронки та кореня 2-го моляру та кореня 3-го моляру. В работе установлено патогенетические особенности состояния системы монооксида азота, врожденного звена местного иммунитета и особенностей протекания регенерации тканей пародонта, определены особенности состояния костной ткани мандибулы, минерализации эмали и дентина моляров без экстракции зуба и в разные периоды после его удаления в условиях экспериментального сахарного диабета. Установлено, что в слизистой оболочке ротовой полости крыс с сахарным диабетом формируется изоформный дисбаланс фермента NOS, отмечаются более низкие исходные значения содержания и концентрации nNOS и еNOS, но значительно выше – iNOS, на фоне высокого исходного уровня нитритов. Доказано особенности экспрессии CD68 и Ki-67 в слизистой оболочке ротовой полости крыс, указывающие на то, что сахарному диабету присуща распространенная макрофагальная инфильтрация и высокая пролиферативная активность фибробластов, из-за чего экстракция зуба незначительно увеличивает экспрессию CD68, но характеризуется высокой пролиферативной активностью сразу после удаления зуба с максимальными значениями Ki-67 на 14-е сутки постэкстракционного периода. При сахарном диабете заживление альвеолярной лунки после удаления зуба происходит неэффективно из-за нарушения резорбционно-репаративных взаимоотношений, проявляется снижением показателя радиологической плотности в области альвеолярной лунки, интеральвеолярных и интеррадикулярных костных перегородок 1-го моляра, коронки и корня 2-го моляра и корня 3-го моляра. In scientific work is defined dynamic complex characteristic of the state of the nitrogen monoxide system, of the innate link of the local immunity and of the peculiarities of the regeneration of periodontium soft tissues, were determined the specific features of mandible bone tissue, mineralization of enamel and dentin of molars without extraction of the tooth, and in different periods after its extraction. It was proved that in the mucous membrane of the oral cavity of rats with diabetes mellitus is forming an isoformal imbalance and a high initial level of nitrites, the concentration of which increases after the extraction of the tooth only on the 7th day and remains stable until the 14th day. According to the results of immunohistochemical studies, it was established that for diabetes mellitus is typical widespread macrophage infiltration, because extraction of the tooth slightly increases the expression of CD68, the process is slow, but is characterized by prolongation in the long-term period. The correlation of NOS isoforms in the oral mucosal membrane of rats with experimental diabetes mellitus is characterized by lower initial values of the content and concentration of nNOS and eNOS, but significantly higher iNOS. It was proved that the tooth extraction on the background of experimental diabetes mellitus is characterized by a moderate increase in the expression of eNOS and nNOS from the 1st till the 7th day, but the decrease on the 14th day. High levels of expression of CD68 and Ki-67 proteins that characterize proliferative and reparative relations in the mucous membrane of the rats’ oral cavity, are also typical for diabetes mellitus. It was found that activated macrophages and proliferative active cells are almost absent in the intact periodontium. At experimental diabetes mellitus, on the contrary, is observed a significant diffuse infiltration of the periodontium soft tissue by macrophages and high proliferative activity; on the 1st day after the extraction of the tooth quantitative characteristics of expression of CD68 don’t change, and Ki-67 significantly increase. In accordance with the results of the radiologic study of the semi mandible of the control group of rats, it was determined that the extraction of the tooth of the rats of control groups with normal carbohydrate metabolism parameters is accompanied by dynamic changes in the radiological density not only in the extraction area, the inflammatory process affects the surrounding 2nd and 3rd molars, resulting in its decrease in areas of inter alveolar and inter radicular septums. The further development received the idea regarding the radiological density of tissues of inter alveolar and inter radicular septums, crowns and roots of the first, second and third molars. It was proved that in mandible bone tissue diabetes mellitus favours the strengthening of resorptive processes characterized by low values of radiological density in the area of the root of the 1st molar by 2.27 times, but high in the area of the inter alveolar and inter radicular septums of all three lower molars, at the same time the alveolus healing after the tooth extraction is happening ineffective because of the damage of resorptive and reparative relations.
Патогенез нарушения механизмов репарации пародонта после экстракции зуба в условиях экспериментального сахарного диабета
Pathogenesis periodontal repair mechanisms disorders after the extraction of a tooth in conditions of experimental diabetes mellitus
Keywords: експериментальний цукровий діабет; екстракція зубу; пародонт; репарація; система монооксиду азоту; Ki-67; CD68; щури; экспериментальный сахарный диабет; экстракция зуба; репарация; система монооксида азота; крысы; experimental diabetes mellitus; tooth extraction; periodontium; reparation; nitrogen monoxide system; rats